Continuing Medical Education Questions: October 2022. (12th October 2022) - Inamdar, Sumant
Abstract : Article Title: Impact of Obesity on Risk of Hospitalization, Surgery and Serious Infection in Biologic-treated Patients with Inflammatory Bowel Diseases (IBD): A CA-IBD Cohort Study